2012
DOI: 10.1016/j.stem.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibition Prevents Epithelial Stem Cell Senescence and Protects from Radiation-Induced Mucositis

Abstract: SUMMARY The integrity of the epidermis and mucosal epithelia is highly dependent on resident self-renewing stem cells, which makes them vulnerable to physical and chemical insults compromising the repopulating capacity of the epithelial stem cell compartment. This is frequently the case in cancer patients receiving radiation or chemotherapy, many of whom develop mucositis, a debilitating condition involving painful and deep mucosal ulcerations. Here, we show that inhibiting the mammalian target of rapamycin (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
223
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(241 citation statements)
references
References 57 publications
15
223
3
Order By: Relevance
“…These results indicate that despite lower mitochondrial content in hepatocytes, mitochondrial function is not significantly altered by mTORC1 inhibition. Recently, it has been suggested that rapamycin may reduce ROS generation via enhanced expression of the antioxidant enzyme MnSOD (Iglesias‐Bartolome et al , 2012), however, we failed to find any changes in MnSOD expression on rapamycin‐fed mice liver tissues (Appendix Fig S3C). …”
Section: Resultscontrasting
confidence: 61%
“…These results indicate that despite lower mitochondrial content in hepatocytes, mitochondrial function is not significantly altered by mTORC1 inhibition. Recently, it has been suggested that rapamycin may reduce ROS generation via enhanced expression of the antioxidant enzyme MnSOD (Iglesias‐Bartolome et al , 2012), however, we failed to find any changes in MnSOD expression on rapamycin‐fed mice liver tissues (Appendix Fig S3C). …”
Section: Resultscontrasting
confidence: 61%
“…Concomitantly, exposure to oxidative stress due to cigarette smoke and chronic inflammation may promote premature cell senescence (5,33). Consistent with this possibility, mTOR was required for oxidative stress-induced cell senescence to occur (17,34), and mTOR activation was associated with oxidative stress in peripheral blood mononuclear cells from patients with COPD (35,36). Previous studies also documented a role of oxidative stress and mTOR activation in response to cigarette smoke exposure (37), and some effects of rapamycin on cell senescence have been related to changes in oxidative stress (17).…”
Section: Discussionmentioning
confidence: 81%
“…Despite this wealth of in vitro data, relatively little is known about the in vivo requirement of actomyosin contractility for desmosomal adhesion and epidermal barrier formation. mTOR signaling perturbation in the epidermis has previously been associated with epithelial carcinogenesis (30), epidermal stem cell senescence (31,32), and delayed wound healing (33). While this article was in preparation, an additional study demonstrated that mTOR kinase and mTORC1 loss of function is associated with impaired epidermal differentiation and barrier formation; however, the molecular mechanism of this finding was not elucidated, and no effects on cell-cell adhesion were described (34).…”
Section: Introductionmentioning
confidence: 91%